PERBEDAAN HASIL BELAJAR DAN AKTIVITAS SISWA DENGAN MODEL PBL DAN IL DENGAN MEDIA HANDOUT PADA MATERI KESETIMBANGAN KIMIA - Nisa Nurul Jannah (Universitas Negeri Medan, 2021)
Differences in Learning Outcomes and Student Activities Using PBL and IL Models with Media Handouts on Chemical Equilibrium Materials. The purpose of this study is to determine: differences in learning outcomes and student activities with Problem Based Learning (PBL) and Inquiry Learning (IL) models with handout media on chemical equilibrium material. This research is conducted using the Pretest-Postest, Nonequivalent Multiple Group Design method which was carried out at Ar-Raudhatul Hasanah Islamic Boarding School. The selected sample used a purposive sampling technique. Data is collected by using pretest and posttest to determine the increase in student learning outcomes and activities, observation sheets to observe student learning activities. Hypothesis I and II are tested using the independent sample t-test technique. Result of research indicate that there is a significant difference in student learning outcomes and activities with PBL and IL models with handout media on chemical equilibrium material.